Analysis of Halal Tourism Potential Based on the 2019 Ministry of Tourism's Halal Tourism Implementation Guidelines (Jung Koneng Bangkalan Mangrove Park) - Kholid (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
The economic sector is one of the most important things in supporting the progress of a country. There are many ways to improve the economy, one of which is by having halal tourism, halal tourism is a tourist spot that refers to the provision of facilities, security, food, and rules in accordance with the provisions of Islamic law, in 2019 Indonesia occupies the first seat as the best halal tourism in world version of the Global Muslim Travel Index (GMTI) overtook 130 other listed countries. Therefore the author sees that the Jung Koneng Bangkalan Mangrove Park has great potential to become halal tourism, so that it can contribute to national economic development, and apply the word hablum minal alam (human relations with nature) by becoming a caliph who looks after and preserves nature which is a decree The Ruler of the Universe. This study uses a qualitative descriptive method and uses an empirical approach, the results obtained are that the Jung Koneng Bangkalan Mangrove Park has the potential to become halal tourism, it's just that there are several sectors that still need to be developed